Promise to return [large type] - Younts, Elizabeth Byler (Younts, Elizabeth Byler. Promise of sunrise, 2014)
It's 1943. Miriam Coblentz and Henry Mast are nearing their wedding day when the unthinkable happens -- Henry is drafted. However, since he is a part of the pacifist Amish tradition, Henry is sent to a conscientious objector Civilian Public Service camp. When he leaves for the work camp, his gaping absence turns Miriam's life upside down. Little does she know it's only the beginning. When Henry returns home, he brings news that shakes Miriam and their Amish community to the core. Henry believes God has called him to enlist in the army and fight for his country, leaving her to make an important decision: whether to choose loyalty to the peaceful life she's always known or her love for Henry. While Henry is battling enemies across the ocean, Miriam struggles between her devotion to Henry and her love of the Amish way of life. One question is at the bottom of it all: will she follow the rules of her religion or the leading of her heart?